2023
DOI: 10.1186/s12894-023-01194-w
|View full text |Cite
|
Sign up to set email alerts
|

RNA-seq reveals novel mechanistic targets of Livin in bladder cancer

Abstract: Background Bladder cancer is a very common malignancy with a high recurrence rate. The survival of patients with muscle-invasive bladder cancer is poor, and new therapies are needed. Livin has been reported to be upregulated in bladder cancer and influence the proliferation of cancer cells. Materials and methods The Livin gene in human bladder cancer cell line T24 was knocked out, and the differentially expressed genes were identified by RNA-seq an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…Previous research has demonstrated that elevated Livin in ovarian cancer cells promotes their proliferation [16] . Additionally, upregulated Livin has been linked to reduced patient survival rates, and that in bladder cancer influences cancer cell proliferation [17] . In addition, this work indicated that upregulation of Livin may be linked to CRC.…”
Section: Resultsmentioning
confidence: 99%
“…Previous research has demonstrated that elevated Livin in ovarian cancer cells promotes their proliferation [16] . Additionally, upregulated Livin has been linked to reduced patient survival rates, and that in bladder cancer influences cancer cell proliferation [17] . In addition, this work indicated that upregulation of Livin may be linked to CRC.…”
Section: Resultsmentioning
confidence: 99%